Neuroprotective effect of Lannea egregia Alkaloid-rich leaf extracts in streptozotocin-induced diabetic rats - B.O. Ajiboye; B.E. Ekundayo; A.W. Salami; A.O. Osukoya; K. Komolafe; S. Gaur; B.E. Oyinloye; T.O. Jeje; O.A. Ojo (Toxicology Reports, 2024)
Background: Studies suggest that medicinal plant extracts can help reduce the neuron degeneration associated with diabetes. In this study, the neuroprotective effect of the alkaloid-rich extract from the leaves of Lannea egregia was assessed in rats with diabetes induced by streptozotocin (STZ). Methods: Lannea egregia alkaloid-rich analysis was carried out via a known procedure. The rats were randomly assigned into five treatment groups (n = 8): normal control, diabetic-induced rats (45 mg/kg STZ), and diabetic rats treated with low doses of Lannea egregia leaf alkaloid-rich extract (50 mg/kg b.w, LEL) and high (100 mg/kg b.w, LEH) (300 mg/kg and 150 mg/kg), and metformin (200 mg/kg). On 22nd day of the experiment, animals were sacrificed, and their blood and brains were collected for neuro-biomarker analysis. Results: Diabetic-induced rats that received metformin, LEL and LEH exhibited considerably reduced levels of dopamine, serotonin, norepinephrine, NO, MDA, and AChE, BChE activities when compared to untreated diabetic animals. Additionally, rats with diabetes that received treatment with metformin, LEL and LEH displayed a noticeable increase in ENTPDase, Na/K ATPase, GST, CAT, GPx, and SOD activities when compared to the untreated diabetic rats. Histological examination revealed improved brain architecture in the treated groups in contrast to those in diabetic-induced rats. Conclusion: The alkaloid-rich extracts of Lannea egregia might be effective in normalizing brain damage caused by complications of diabetes mellitus.